Reinterpretation of a Middle Eocene Record of Tardigrada (Pilosa, Xenarthra, Mammalia) from La Meseta Formation, Seymour Island, West Antarctica - MacPhee, R. D. E.; Reguero, Marcelo Alfredo
An isolated and incomplete tooth, discovered in sediments of Middle Eocene La Meseta Fm on Seymour Island (northern Weddell Sea, West Antarctica), has previously been interpreted to be that of a sloth. The specimen as preserved is composed of dentine, as in sloths and tooth-bearing xenarthrans generally. However, characters associated with the dentinal histology of definite sloths are either not represented on the Seymour tooth, or depart considerably from tardigradan and even general xenarthran models according to new observations presented here. On the basis of histological criteria, the La Meseta tooth cannot be shown positively to be tardigradan; it may not even be xenarthran. Further progress with establishing its relationships will depend on the recovery of more (and better) specimens. For the moment, it is best attributed to Mammalia, incertae sedis. Fil: MacPhee, R. D. E. American Museum of Natural History; Estados Unidos Fil: Reguero, Marcelo Alfredo. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina